La práctica indebida de actos de naturaleza sexual en público y la inexistencia de una sanción que condene este tipo de actos contrarios a la moral social - Jiménez Vera., Melany Solange (2024)
The present work called: “The improper practice of acts of a sexual nature in public and the lack of a sanction that condemns this type of acts contrary to social morality”; arises as a result of the social alarm that has been triggered in recent times by the practice of sexual relations, touching, and other manifestations of a sexual nature in public, and of the regulatory insufficiency that, with respect to this type of behavior, has been possible. verify within our criminal legislation. Such a situation has determined the need to carry out a legal, doctrinal and comparative study of the legal figure of outrage to public modesty, as a form of response to this type of actions, which forced us in the first instance to verify that this crime, does not It is typified in our criminal legal system, the comparative legal framework that regulates outrage to public modesty in Latin American legislation and finally the possibility of verifying whether the type of conduct mentioned meets the necessary conditions to be considered a criminal offense in our country. For this purpose, the documentary technique has been used as a way to catalog the information produced and prepared by the legislator (norms), the judge (resolutions) and the academic (doctrine), in terms of concepts such as public modesty, morality social, the right to sexual indemnity and sexual integrity of people, so that they allow us to expand our knowledge of these principles and rights; and, its relationship with the outrage of public modesty. Finally, the criteria obtained based on the doctrinal, theoretical and legal compilation were contrasted with our social performance through the development of surveys and interviews, which allowed us to reach concrete conclusions and propose a reform proposal.